Mydriasis as a sole sign of siderosis bulbi resulting from an unnoticed trauma and intraocular metallic foreign body - (:unkn) unknown (Gazi Eye Foundation, 2019)
We aimed to report a case of unnoticed, retained metallic intraocular foreign body that did not show any findings of the ocular siderosis but mydriasis initially. An 8-year-old boy was referred to our clinic for monocular mydriasis. The child as well as the parents denied any recent or past trauma history to the eye. An intraocular foreign body was detected at cranial computed tomography. After the removal of the intraocular foreign body, mydriasis recovered, however, due to the development of proliferative vitreoretinopathy, eventual functional success was poor after several vitrectomies. In conclusion, intraocular foreign body and iron mydriasis should be kept in mind in the differential diagnosis of a dilated and fixed pupil and treatment-resistant uveitis. © 2019 Gazi Eye Foundation. All rights reserved.
Keywords: Intraocular foreign body; Mydriasis; Ocular siderosis; Retinal detachment; Trauma